Palma forrageira (Opuntia fícus-indica Mill) associada a diferentes silagens na alimentação de vacas lactantes da raça Sindi - Sobral, Acir José Santos (2020)
The forage “prickly pear” (Opuntia ficus-indica Mill) is an important forage resource for the Brazilian Northeast Region, due to its adaptation to the edaphoclimatic conditions of the region, especially in the dry periods. The present study aimed to investigate the effects of diets of forage prickly pear associated with different fiber sources in the intake (dry matter and water), digestibility, microbial protein production, nitrogen compound balance and performance of Sindi dairy cows reared in semiarid regions. The silages used were: atriplex (Atriplex numulária Lindi.), forage sorghum (Sorghum bicolor (L.) Moench), gliricídia (Gliricidia sepium (Jacq.) Walp. ) and maniçoba (Manihot pseudoglaziovii Pax & K. Hoffm.) which were included in diets based on forage prickly pear (ratio 58:42 forage: concentrate). The cows were distributed in a double 4x4 Latin Square design lasting 12 days each period. For water ingestion there was difference (P<0.05) for the diet containing atriplex silage (19.42 L/d). The diet with sorghum silage showed lower (P<0.05) dry matter digestibility coefficient (48.71 %) then the treatment with atriplex silage (68.46%). The lowest amount of milk protein was found in the treatment with gliricidia silage (38.9 g/kg). The diet with atriplex silage showed higher (P<0.05) urine excretion (8.43L/day) compared to the treatment with gliricidia silage (13.92 mmol/day). There was a difference (P<0.05) in the allantoin:purine-derived ratio in the treatment with gliricidia silage. Microbial synthesis was higher (P<0.05) in diet with atriplex silage compared to the treatment containing gliricidia silage (115.01 and 80.07 g Of PBmic/kg of TDN, respectively),. Lower nitrogen intake was observed in the diet with gliricidia silage (182.95 g/day) in relation to the diet with sorghum silage (212.84 g/day). Nitrogen balance was positive and was not influenced by the diets. The evaluated silages associated with forage palm can be used in diets for Lactating Sindi cows without influencing daily dry matter intake, altering milk production and fat, microbial protein synthesis and nitrogen compound balance.